Influencer dan Strategi Penjualan: Studi Netnografi pada Pengguna Jasa Selebgram sebagai Media Promosi - Nasih, Muhammad; Susanto, Otto Masyad; Fanshury, Abdul Roziq; Hermawan, Sigit (Benefit: Jurnal Manajemen dan Bisnis, 2020)
The business is undergoing many changes including the media used as promotion. The existence of advertisements on television began gradually abandoned and shifted to a new strategy, namely advertising on social media. The rapid growth of social media users in Indonesia has become one of the factors in the change. This study aims to determine the extent of the impact of using influencers as a promotion strategy on social media, especially Instagram. This study uses a qualitative netnographic method by collecting data through observation of social media accounts and in-depth interviews from informants. The results of this study include illustrating that there are positive and negatif impacts from the use of influencer services. Companies must be smart in choosing influencers that are in line with product segmentation, price, and influencer's background because people are now getting smarter at making purchases. Â